Blood Transfusion Requests: An Audit in a Blood Transfusion Wing of a Referral Laboratory (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Transfusion of blood and its components such as Packed Red Cell (PRC), Platelet Rich Plasma (PRP) and Fresh Frozen Plasma (FFP) play an important role as a supportive therapy in patients admitted to a hospital.Objective: To conduct an audit of blood transfusion requests regarding demographic data of the recipients, the component therapy, blood groups of the issued units, cross-match transfusion ratio, expiry of the transfusion units, pattern of blood components usage and transfusion reaction for which blood was returned back to blood bank.Materials and Methods: This retrospective crosssectional study was conducted at the transfusion wing of a referral laboratory over a period of three months from January 2013 to March 2013 upon 3015 episodes of transfusion units of whole blood and different blood components.Results: Out of total 3015 episodes of transfusion unit in 1926 recipients, 930 were male and 996 female. About 41.0% requests of transfusion units received from the department of Obstetrics and Gynaecology (OBG) followed by the department of Surgery of about 28.7%. The most commonly used transfusion units was whole blood (55.3%) followed by platelet rich plasma (27.2%). Most of the recipients (62.3%) received single transfusion units and 37.7% recipients of ≥2 units. Out of 3769 cross-match, 3015 transfusion units were issued. In 12 (0.4%) cases, there were minor febrile and allergic reactions. During the study period, shelf life of six transfusion units had expired.Conclusion: This study suggests that either systems audit or medical practice audit of blood and blood component orders can help to reduce the inappropriate or indiscriminate transfusions and may be an important educational tool for the ordering physicians as well as for residents in trainingJournal of Armed Forces Medical College Bangladesh Vol.11(2) 2015: 3-6